A study on awareness on tuberculosis among urban slum population of Hyderabad - A., Sai Ram; M. N., Rama Krishna; Singh C., Sunil Pal (International Journal Of Community Medicine And Public Health, 2020)
Background: Tuberculosis a major public health problem in India with highest burden of cases. India accounts for about 24% of global prevalence, 23% of the global incidence cases and 21% of global TB deaths. Irregular and inappropriate treatment of persons with active TB, unawareness about TB symptoms and treatment course, illiteracy, may be the major hurdles for TB eradication. Methods: A cross sectional, community based study was conducted in urban slum dwellers (n=153). Data compilation and analysis: All the data collected was entered and analyzed with MS excel software 2007 and Epi info 3.5.3. All tests were considered significant at p<0.05 level. Results: 18.3% told that cough+expectoration+evening rise of temperature+weight loss are the signs and symptoms of TB. 55.5% know that it spreads through cough and sneezing mixed with air. 23.5% knows blood examination, sputum examination, X-ray is the mode of diagnosis of TB. Conclusions: Literacy plays major role in creating awareness on TB.